Manejo reprodutivo de suínos criados em sistema intensivo confinado - IFTO – Araguatins-TO - Sousa, Luciana de Oliveira (Universidade Federal do Tocantins, 2023)
The supervised curricular stage developed was conducted in the swine sector, the Federal Institute of Education, Science and Technology, Araguatins - TO, under the guidance of Professor Dr. Gerson Fausto da Silva and teacher supervision MSc. Alfonso Siqueira D’imperio, conducted of between April 24, 2014 to June 24, 2014, the current swine search, continuously, increase reproductive efficiency. Thus, the technician needs to know the reproductive aspects that characterize the species. And so apply good management within the production system, ensuring a greater number of piglets weaned / sow / year and good income producer. The activities performed during the probationary period were related to reproductive management adopted by the farm until the weaning phase, feed management reproduction, cleaning and disinfection of premises and Control record in confined-system intensive breeding.